A lifespan development perspective and meta‐analysis on the relationship between age and organizational training. Issue 4 (4th July 2022) - Davenport, Meghan K.; Young, Carmen K.; Kim, Michelle H.; Gilberto, Jacqueline M.; Beier, Margaret E.
Abstract: The confluence of the aging population and economic conditions that require working longer necessitate a focus on how to best train and develop older workers. We report a meta‐analysis of the age and training relationship that examines training outcomes and moderators with 60 independent samples (total N  = 10, 003). Framed within the lifespan development perspective, we expected and found that older trainees perform worse ( ρ  = −.14, k  = 34, N  = 5642; δ  = 1.08, k  = 21, N  = 1242) and take more time ( ρ  = .19, k  = 15, N  = 2780; δ  = 1.25, k  = 12, N  = 664) in training relative to younger trainees. Further, age was negatively related to post‐training self‐efficacy ( ρ  = −.08, k  = 10, N  = 4631), but not related to trainee reactions. Moderator analyses provided mixed support that training alone is related to increased mastery of skills and knowledge. No support was found for the moderating effects of pacing or instructional approach. We call for future research examining the interactive effects of training design on older worker outcomes in ways that capitalize on age‐related growth, compensate for decline, and consider the strategies workers use to mitigate the effect of age‐related losses.